The significance of play in the art gallery interactive environment: A case study of Nathaniel Stern's Stuttering (2003) and Step Inside (2004) - Bland, Catherine Jane (My University, 2009)
Abstract The incorporation of playful interactive artworks into the art gallery affords gallery viewers an opportunity to break away from traditional art gallery viewing practices. Understanding the consequences of this break requires an analysis of the rules of the art gallery and a reassessment of the role of the gallery viewer. By providing a historical perspective on the gallery, its evolution over time and the changing roles of its viewers, along with an understanding of theories concerning the concept of play in general and, more specifically, the concept of play in the gallery, this report aims to prove that play is a serious and meaningful activity allowing contemporary art consumers a more profound experience of an artwork than that enabled by traditional art viewing practices. Using a case study of Nathaniel Stern’s interactive artworks, Stuttering (2003) and Step Inside (2004), this report assesses the use of bodily play in the art gallery and outlines some misconceptions with regard to the incorporation of play into this environment. These interactive artworks transform the viewer’s understanding of an artwork from something that is mentally and visually appreciated, to something that can be tangibly and physically experienced and appreciated. The report concludes that the viewer’s role in this environment has shifted, and that a new conceptualisation or classification of this role has become necessary.